DriveGuard: enhancing vehicle breakdown assistance through mobile geolocation technology - Ariff, Mohamed Imran Mohamed; Halim, Abdul Hadi Abdul; Ahmad, Samsiah; Abdullah, Mohammad Nasir; Zulkifli, Zalikha; Salleh, Khairulliza Ahmad (International Journal of Electrical and Computer Engineering (IJECE), 2025)
The DriveGuard mobile application addresses the growing demand for efficient vehicle breakdown assistance by connecting users to nearby workshops using advanced geolocation technologies. With the rise in private vehicle ownership, sudden breakdowns are increasingly common, necessitating quick access to assistance. DriveGuard utilizes GPS, GSM/CDMA Cell IDs, and Wi-Fi positioning for precise location tracking, enabling users to locate assistance rapidly and accurately. Developed through the waterfall model, the application offers a user-friendly interface built with the Flutter framework. Test results indicate high functionality and user satisfaction, achieving usability ratings between 88% and 90%. DriveGuard’s design improves road safety by reducing waiting times for emergency services, alleviating the stress often associated with breakdown situations. Future work will focus on expanding service options, enhancing security, and refining user interactions to provide a more comprehensive roadside assistance tool. DriveGuard demonstrates the potential of mobile technology in promoting safe and efficient transportation.